1999
DOI: 10.1021/bi991771m
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet Damage and Nucleosome Folding of the 5S Ribosomal RNA Gene

Abstract: The Xenopus borealis somatic 5S ribosomal RNA gene was used as a model system to determine the mutual effects of nucleosome folding and formation of ultraviolet (UV) photoproducts (primarily cis-syn cyclobutane pyrimidine dimers, or CPDs) in chromatin. We analyzed the preferred rotational and translational settings of 5S rDNA on the histone octamer surface after induction of up to 0.8 CPD/nucleosome core (2.5 kJ/m(2) UV dose). DNase I and hydroxyl radical footprints indicate that UV damage at these levels does… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
33
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 37 publications
4
33
0
Order By: Relevance
“…This study used the 5S rDNA nucleosome positioning sequence with uracil residues at sites more than two or five helical turns away from the dyad center. As observed by these authors (54), a feature of 5S rDNA nucleosomes, demonstrated previously by others (55)(56)(57)(58)(59), is the presence of multiple translational settings of the DNA on the histone octamer surface. Thus, the transient exposure of uracil by variability in translational setting of the 5S rDNA, as well as increased ''breathing'' of DNA away from the dyad center of nucleosomes (8,52), makes the results of Nilsen et al (54) more difficult to interpret.…”
Section: Discussionsupporting
confidence: 63%
“…This study used the 5S rDNA nucleosome positioning sequence with uracil residues at sites more than two or five helical turns away from the dyad center. As observed by these authors (54), a feature of 5S rDNA nucleosomes, demonstrated previously by others (55)(56)(57)(58)(59), is the presence of multiple translational settings of the DNA on the histone octamer surface. Thus, the transient exposure of uracil by variability in translational setting of the 5S rDNA, as well as increased ''breathing'' of DNA away from the dyad center of nucleosomes (8,52), makes the results of Nilsen et al (54) more difficult to interpret.…”
Section: Discussionsupporting
confidence: 63%
“…44). On the other hand, irradiation was shown to destabilize nucleosomes reconstituted on 5 S rDNA (45) and plasmids (46), whereas nucleosomes reconstituted on HISAT DNA and 5 S rDNA were not similarly affected (20,38,39). In the examples shown in this study, UV lesions were not sufficient to disrupt the nucleosomes.…”
Section: Resultsmentioning
confidence: 56%
“…CPD formation depends on the structure of DNA and can be altered by folding of DNA in nucleosomes (37)(38)(39). ATDED-long nucleosomes were analyzed by UV photo-footprinting during remodeling (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…8); however, past biochemical and cellular studies have suggested that nucleosomes and DNA-binding proteins may significantly alter the formation of UV damage (11)(12)(13)(14). Previous attempts to measure initial CPD levels using microarray-based methods (15)(16)(17) suggested that UV damage formation is primarily influenced by the DNA sequence.…”
mentioning
confidence: 99%